2021
DOI: 10.1021/acs.jmedchem.1c00678
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, Synthesis, and Evaluation of Highly Selective Vascular Endothelial Growth Factor Receptor 3 (VEGFR3) Inhibitor for the Potential Treatment of Metastatic Triple-Negative Breast Cancer

Abstract: We herein report the identification, structural optimization, and structure−activity relationship of thieno[2,3d]pyrimidine derivatives as a novel kind of selective vascular endothelial growth factor receptor 3 (VEGFR3) inhibitors. N-(4-Chloro-3-(trifluoromethyl)phenyl)-4-(6-(4-(4-methylpiperazin-1yl)phenyl)thieno[2,3-d]pyrimidin-4-yl)piperazine-1-carboxamide (38k) was the most potent VEGFR3 inhibitor (IC 50 = 110.4 nM) among developed compounds. Compared with VEGFR1 and VEGFR2, VEGFR3 was approximately 100 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…It shows that integrated traditional Chinese and Western medicine treatment can improve the immune function of patients with oral cancer, which may improve the therapeutic efficacy. Previous studies have also shown that integrated traditional Chinese and Western medicine treatment improves the therapeutic efficacy of patients with oral cancer, improves the patient's immunity, and brings new hope for the treatment of patients with oral cancer [ 19 , 24 , 25 ]. Traditional Chinese medicine has a very good therapeutic position in the treatment of breast cancer, gastric cancer, and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that integrated traditional Chinese and Western medicine treatment can improve the immune function of patients with oral cancer, which may improve the therapeutic efficacy. Previous studies have also shown that integrated traditional Chinese and Western medicine treatment improves the therapeutic efficacy of patients with oral cancer, improves the patient's immunity, and brings new hope for the treatment of patients with oral cancer [ 19 , 24 , 25 ]. Traditional Chinese medicine has a very good therapeutic position in the treatment of breast cancer, gastric cancer, and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation inhibitory activity of the synthesized pyrazinyl–aryl urea derivatives was assessed using the MTT assay, according to the previous report. 49 Human cancer cell lines including Hep G2, MGC-803, T24, NCI-H460, and PC-3 were purchased from the Typical Culture Preservation Committee Cell Bank of the Chinese Academy of Science (Shanghai, China). Normal bladder epithelial cell line HCV29 was provided by the Department of Cell Biology, Institutes of Medical Sciences, Shanghai Jiao Tong University School of Medicine.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Most VEGFR inhibitors are not VEGFR3 selective. However, new ERK inhibitors and highly selective VEGFR3 inhibitors have been developed and are currently under investigation [ 41 , 42 ]. The novel agents may be candidate anti-invasive drugs for treating pNETs.…”
Section: Discussionmentioning
confidence: 99%